DIGITAL COMPETENCES LEVEL OF INDONESIAN TEACHERS IN PROFESSIONAL LEARNING COMMUNITY - Mohamad Zaenuri Ari (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2023)
The education practices also changed for the past 20 years because the introduction of technology. Digital competences become an important goal to teachers’ development. Professional Learning Community that become a central development of teachers’ knowledge and practice must also implement the digital competences. This study aims to determine the digital competences level of Indonesian teachers based on the DigCompEdu framework, and teachers’ experience effect on their digital competence level. The data gathered by using translated version of Check-in tool. This research used descriptive statistics analysis. The research conducted in one of the professional teacher associations in Indonesia. The result shows that most teachers are still in the Exploration and Integration phase, 43% majority of Integrator levels and 17.2% of Exploration levels, also 26.9% Expert level, and 6,5% each of The Leader and Pioneer levels. Indonesian teachers need more opportunities to develop their digital competence, hence the more experienced teacher has consistent of high-level teachers. PLC on this note could become a central of teachers’ digital competence development by collaborating with teachers in the different digital competence level